2022
DOI: 10.1108/he-03-2021-0046
|View full text |Cite
|
Sign up to set email alerts
|

Becoming accustomed to online teaching: nursing lecturers' experiences in the era of COVID-19

Abstract: PurposeThis study aimed to explore nursing lecturers' experiences of online teaching and learning during the coronavirus disease 2019 (COVID-19) pandemic. The COVID-19 policy on social and physical distancing urges nursing lecturers to provide online teaching delivery for their students using both synchronous and asynchronous methods. However, the experiences of nursing lecturers providing online teaching delivery in the era of COVID-19 are yet unknown.Design/methodology/approachThe authors used an interpretiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Previous research supports similar findings (Ligita et al, 2022;Rasheed et al, 2020). Ligita et al's (2022) study reported pivoting to online teaching requires digital technologies, including video conferencing, on-line forums, multimedia programs and devices and a greater reliance on learning management systems and other platforms for synchronous and asynchronous learning (Ligita et al, 2022).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous research supports similar findings (Ligita et al, 2022;Rasheed et al, 2020). Ligita et al's (2022) study reported pivoting to online teaching requires digital technologies, including video conferencing, on-line forums, multimedia programs and devices and a greater reliance on learning management systems and other platforms for synchronous and asynchronous learning (Ligita et al, 2022).…”
Section: Discussionmentioning
confidence: 73%
“…Ligita et al's (2022) study reported pivoting to online teaching requires digital technologies, including video conferencing, on-line forums, multimedia programs and devices and a greater reliance on learning management systems and other platforms for synchronous and asynchronous learning (Ligita et al, 2022). Ensuring academics were skilled in using the array of contemporary digital technologies for teaching was vital to ensure quality student learning and engagement, and flexible programs for delivering high-quality materials for teaching required familiarity with technology, user-friendly infrastructure and digital interfaces for both students and staff (Ligita et al, 2022;Rasheed et al, 2020). However, support for the three stakeholders; academics, students and Universities is needed for this to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…The findings underscore the significance of technological competence and the potential for advancements in online teaching practices in nursing education. [Ligita, T., Mita, Murtilita and Winarianti (2022)].…”
Section: Literature Reviewmentioning
confidence: 99%